Colonization or urbanization: Towards a detailed analysis of the transformation of tourism space based on the districts of Kołobrzeg - Miedziński, Mariusz (Who needs tourism?, 2024)
The city of Kołobrzeg is the largest health resort in Poland and at the same time one of the most important tourist centers (along with Warsaw, Krakow and Tricity). The volume of recorded tourism results from the exceptionally intense concentration of accommodation facilities and the level tourist colonization reached. In the light of research conducted in Kołobrzeg, part of the area of tourist colonization subspace is being transformed into tourist urbanization subspace. Research on the process of transformation required the use of detailed geodemographic data regarding the location of registration addresses and the distribution of population according to statistical units and census districts. The obtained geodemographic data are consistent with the issues of research on the scale of the expansion of the tourist accommodation base, as well as the location and use of existing housing and apartment resources across time. This has made it possible to geolocate places and areas of registration for residents and examine changes in the population distribution for nine districts in the years 2017–2023. As a result of the detailed research, an attempt is made to extrapolate the expansion of Kołobrzeg for residents and possible changes in the capacity of tourist accommodation: 2023–2035. The results confirmed changes to tourist space and the progressive functional specialization of individual districts. It should be emphasized that ongoing changes in its tourist space are closely related to changes in the city’s socio-economic profile and its functional transformation. Kołobrzeg is therefore a very interesting case study of the rapid socio-economic development of a previously monofunctional medium-sized settlement which, despite the negative effects of the COVID-19 pandemic and changes taking place in the socio-economic and political environment (e.g. the war in Ukraine), is constantly expanding its importance on a national scale and in particular in Central and Western Pomerania.